2020
DOI: 10.3390/cells9092088
|View full text |Cite
|
Sign up to set email alerts
|

The Amazonian Red Side-Necked Turtle Rhinemys rufipes (Spix, 1824) (Testudines, Chelidae) Has a GSD Sex-Determining Mechanism with an Ancient XY Sex Microchromosome System

Abstract: The Amazonian red side-necked turtle Rhynemis rufipes is an endemic Amazonian Chelidae species that occurs in small streams throughout Colombia and Brazil river basins. Little is known about various biological aspects of this species, including its sex determination strategies. Among chelids, the greatest karyotype diversity is found in the Neotropical species, with several 2n configurations, including cases of triploidy. Here, we investigate the karyotype of Rhinemys rufipes by applying combined conventional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 81 publications
1
16
0
Order By: Relevance
“…Usually, microsatellites accumulations were demonstrated in the terminal regions of vertebrate chromosomes, which seems to be a common feature due to different mechanisms that accumulate these sequences in these regions ( Pokorná et al ., 2011b ; Torres et al ., 2011 ; Ruiz-Ruano et al ., 2015 ; Ernetti et al ., 2019 ; Lee et al ., 2019 ; Viana et al ., 2020 ). The (CA) n , (GA) n , (CAG) n and (GATA) n microsatellites were reported for the first time in sea turtle’s karyotypes and demonstrated that most of them possibly make up part of the repetitive units of heterochromatin in C. mydas, C. caretta , L. olivacea and E. imbricata , especially in mc.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Usually, microsatellites accumulations were demonstrated in the terminal regions of vertebrate chromosomes, which seems to be a common feature due to different mechanisms that accumulate these sequences in these regions ( Pokorná et al ., 2011b ; Torres et al ., 2011 ; Ruiz-Ruano et al ., 2015 ; Ernetti et al ., 2019 ; Lee et al ., 2019 ; Viana et al ., 2020 ). The (CA) n , (GA) n , (CAG) n and (GATA) n microsatellites were reported for the first time in sea turtle’s karyotypes and demonstrated that most of them possibly make up part of the repetitive units of heterochromatin in C. mydas, C. caretta , L. olivacea and E. imbricata , especially in mc.…”
Section: Discussionmentioning
confidence: 99%
“…Dmrt1 is a gene that acts during sex determination stages in reptile development ( Kettlewell et al ., 2000 ; Mizoguchi and Valenzuela, 2020 ), in which the sex of the embryos is determined by the incubation temperature of the nest (temperature-dependent sex determination: TSD), the most common mechanism of environmental sex determination (ESD) ( Ferreira Júnior, 2009 ). Although, genotypic sex determination was described to have evolved independently in five families of turtles (Chelidae, Emydidae, Geoemydidae, Kinosternidae and Trionychidae) (Valenzuela and Adams, 2011 , Valenzuela et al , 2014 ; Badenhorst et al ., 2013 ; Rovatsos et al ., 2017 ; Lee et al ., 2019 ; Viana et al ., 2020 ), sea turtles were described as belonging to a TSD lineage ( Bickham et al ., 1980 ; Morreale et al ., 1982 ; Yntema and Mrosovsky, 1982 ; Mrosovsky et al ., 1984 , 1992 ; Valenzuela and Adams, 2011 ; Montiel et al ., 2016 ). Previous in situ localization of (GATA) n in three species of turtles with TSD, using both sexes, detected markers preferably in mc and without evidence of sex-specific chromosomal sites ( Mazzoleni et al ., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations